Is the Eurozone disintegrating? Macroeconomic divergence, structural polarisation, trade and fragility. (15th January 2020) - Gräbner, Claudius; Heimberger, Philipp; Kapeller, Jakob; Schütz, Bernhard
Abstract: This paper analyses macroeconomic developments in the Eurozone since its inception in 1999. In doing so, we document a process of divergence and polarisation among those countries that joined the Eurozone during its first two years. We find evidence for a 'core–periphery' pattern among Eurozone countries, that is, however, marked by substantial heterogeneity within these two clusters. We show how the polarisation process underlying this pattern first manifested in increasing current account imbalances, before it translated unto the level of general macroeconomic development when the crisis hit. Empirically, we demonstrate how this macroeconomic divergence is tied to a 'structural polarisation' in terms of the sectoral composition of Eurozone countries; specifically, the emergence of export-driven growth in core countries and debt-driven growth in the Eurozone periphery can be traced back to differences in technological capabilities and firm performance. Pushing for convergence within Europe requires the implementation of industrial policies aiming at a technological catch-up process in periphery countries in combination with public investment and progressive redistributional policies to sustain adequate levels of aggregate demand in all Eurozone countries.